Klasifikasi Hama Yang Menyerang Tanaman Petani Berbasis Augmented Reality Menggunakan Metode Marker Based - Ricky Zulianto Pasaribu; Ari Usman; Sarudin (Universitas Harapan Medan, 2021)
The most food crops planted by farmers, one of which is rice, which is one of the crops for food needs in Indonesia, rice plants are plants that are very much planted by farmers due to the basic needs of Indonesian food for the main food source. However, this rice is easily attacked by rice pests which are harmful organisms with the necessities of life to need shelter and food for the rice plants that are cultivated by farmers, attacks by rice pests that make the economic producers of farmers low as a result of such a large pest attack. to the plant. With the use of Augmented Reality technology for the introduction of rice pests and will facilitate the delivery of pest information in the form of virtual 3D animation and inform various types of shapes and pests that attack rice plants, the use of this Augmented Reality application that uses markers to bring up 3D objects that can detect markers with a distance of 20-30 cm by using Vuforia to register images on the vuforia website. With this application it helps people to recognize the effects of pest attacks that have damaged the rice plant, by building this application it will help people who are not familiar with the type of rice pest to become familiar with it so that it will make it easier for people to see rice pests virtually in the form of 3D animation that will be displayed from the 2D marker detected from the cellphone camera